AB0440 What effect does the presence of bronchiectasis have on CCP antibody levels in patients with rheumatoid arthritis?. (23rd January 2014) - Moullaali, T.; Perry, E.; Hutchinson, D.; Hamilton, J.; Kelly, C.
Abstract : Background: It is well established that anti cyclic citrullinated peptide (CCP) antibodies are a marker of rheumatoid arthritis (RA) and are associated with greater articular damage [1]. There is increasing evidence to suggest that they may also be related to systemic complications of RA, especially those affecting the lung [2]. Recently, CCP antibodies have been reported in the presence of chronic infection. We wondered if the presence of bronchiectasis might affect the levels of CCP antibody in RA patients? Objectives: To measure the levels of anti CCP antibody in patients with RA and compare those found in patients with and without bronchiectasis in order to assess the possible influence of chronic pulmonary infection on CCP antibody production. Methods: We identified 23 patients with RA and bronchiectasis from our hospital database. All these index patients met the recent EULAR guidelines for RA and had the presence of bronchiectasis confirmed on high resolution computed tomography. We then identified 23 case controls with RA on EULAR criteria who were matched for age and gender with each index case. We recorded smoking status and history for each patient. We then measured anti CCP antibody levels in all patients (normal range 0-7 U/ml), and compared the results between the two groups using Chi squared statistics and Students paired t testing after ensuring uniform distribution. Results: Patients with RA and bronchiectasis had a mean age of 66 (54 - 79 years), with a male to female ratio of 11:12. The RA patients with bronchiectasis were positive for the presence of CCP antibodies in 83% of cases, and mean levels were 158.6 U/ml (SE 29.9). By contrast, RA patients without bronchiectasis had a positivity rate of 54% [p=0.013], with a mean value of 57.9 U/ml (SE 24.1) [p=0.003]. However, the groups also showed a difference in smoking history with just 33% of bronchiectasis patients having never smoked, as opposed to 72% of RA controls, although none of the index cases were still smokers at the time of the study. Cumulative smoking in pack years was not significantly different between the groups. Conclusions: These data show an association between chronic lung infection in the form of bronchiectasis and anti CCP antibody status in RA patients. This may be partly explained by smoking. Further studies in non smokers and in patients with chronic lung infection without RA are required to define the potential relevance of this. However, these data add weight to the growing suspicion that the lungs may be an important portal for the acquisition of antigens triggering autoimmune responses in RA [3]. References: Jansen LM, van Schaardenburg D, van der Horst-Bruinsma I, van der Stadt RJ, de Koning MH, Dijkmans BA, The predictive value of anti-cyclic citrillunated peptide antibodies in early arthritis. J Rheumatol 2003;30: 1691-5 Alexiou I, Germenis A, Koutroumpas A et al. Anti-cylcic citrullinated peptide (CCP) antibodies and extra articular manifestations in Greek patients with rheumatoid arthritis. Clin Rheumatology 2008; 27: 511-3 Demoruelle M, Weisman M, Derber L et al. Lung abnormalities in subjects with elevations of Rheumatoid Arthritis-related autoantibodies without arthritis by examination and imaging suggest the lung is an early and perhaps initiating site of inflammation in rheumatoid arthritis ACR 2011 Abs. 769 Disclosure of Interest: None Declared